The Relationship Between Lifestyle and Conformity With Consumption Behavior in Adolescents - Aida Fahkrunnisa Nuhdi Alwi; Siti Nurina Hakim (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2023)
Excessive shopping activities lead to consumptive behavior, the cause of consumptive behavior due to the environment and high lifestyle that encourage someone to look luxurious. This study aims to determine the relationship between Lifestyle and Conformity with Consumptive Behavior in Adolescents. The research hypotheses are: (1) There is a relationship between Lifestyle and Conformity with Consumptive Behavior in Adolescents; (2) There is a positive relationship between Lifestyle and Consumptive Behavior in Adolescents; (3) There is a positive relationship between conformity and consumer behavior in adolescents. The research method uses quantitative methods with Consumptive Behavior as the dependent variable, the independent variables are Lifestyle and Conformity. The research population of the Surakarta City community with a sample of 100 respondents was determined by purposive quota sampling technique. The data analysis technique used multiple linear regression. The results of the analysis of Lifestyle and Conformity with Consumptive Behavior in Adolescents (R)=0.847 sig.p=0.000(p0.01) there is a very significant relationship between Lifestyle and Conformity with Behavior in Adolescents, Lifestyle and Consumptive Behavior (r) = 0.843 sig.p=0.000(p0.01) there is a very significant positive relationship between Lifestyle and Consumptive Behavior in Adolescents, Conformity with Consumptive Behavior (r)=0.461 sig.p=0.000(p0.01) there is a very significant positive relationship between conformity with Consumptive Behavior in Adolescents. Accuracy in groups and administration.